CATALYST AND METHOD FOR PRODUCING COMPOUND USING THE SAME

By employing a catalyst with a high SPHT3 value and a specific composition supported on an inert carrier, the challenges of achieving high selectivity in the gas phase catalytic oxidation of propylene and butenes are addressed, resulting in improved yield and stability.

JP7649427B2Active Publication Date: 2025-03-19NIPPON KAYAKU CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2024521355
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-12-20
Filing Date
2023-12-13
Publication Date
2025-03-19
Estimated Expiration
2043-12-13

AI Technical Summary

Technical Problem

Current technologies face challenges in achieving sufficient selectivity during the gas phase catalytic oxidation of propylene, isobutylene, t-butyl alcohol, and butenes to produce unsaturated aldehydes, unsaturated carboxylic acids, and 1,3-butadiene, leading to inefficient production and stability issues.

Method used

A catalyst with a spherical parameter SPHT3 of 0.9822 or more, obtained through dynamic image analysis, is used. The catalytic active ingredient is composed of specific elements such as molybdenum, vanadium, tungsten, copper, antimony, and oxygen, with precise atomic ratios, supported on an inert carrier like silica or alumina.

Benefits of technology

This approach maintains high selectivity in the production of unsaturated aldehydes and unsaturated carboxylic acids, enhancing yield and stability, while also reducing by-products, thus improving the carbon neutrality of the process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007649427000003
    Figure 0007649427000003
  • Figure 0007649427000004
    Figure 0007649427000004
  • Figure 0007649427000005
    Figure 0007649427000005
Patent Text Reader

Abstract

The present invention pertains to a catalyst in which the value of a spheroidicity parameter SPHT3 determined by a particle shape measurement using a dynamic image analysis method is 0.9822 or more. Here, the spheroidicity parameter SPHT3 is a value obtained from formula (I). (I): SPHT3=4πA / P2 In formula (I), A represents the area of particles imaged by the dynamic image analysis method, and P represents the outer circumference length of the particles.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a novel catalyst capable of obtaining a target product with high selectivity, and in particular to a catalyst that enables stable and high-yield production when an unsaturated aldehyde, an unsaturated carboxylic acid, or a conjugated diene is oxidatively produced. [Background technology]

[0002] Methods for producing corresponding unsaturated aldehydes and unsaturated carboxylic acids using propylene, isobutylene, t-butyl alcohol, etc. as raw materials, and vapor-phase catalytic oxidation methods for producing 1,3-butadiene from butenes are widely used industrially. In particular, many reports have been published on methods for producing corresponding unsaturated aldehydes and unsaturated carboxylic acids using propylene, isobutylene, t-butyl alcohol, etc. as raw materials as means for improving the selectivity.

[0003] Acrylic acid in particular is becoming increasingly important as a raw material for absorbent resins, adhesives, etc. For this reason, in recent years, there has been a demand for improved catalyst performance for producing acrylic acid by gas-phase catalytic oxidation reaction using acrolein as a raw material. Accordingly, various companies have been making various improvements to catalysts that can produce acrylic acid stably in high yields for a long period of time, and for example, the following have been proposed:

[0004] Patent documents 1 to 3 disclose improvements in catalyst composition, etc., focusing on the X-ray diffraction peaks of catalytically active components. These catalysts have been proposed as catalysts that achieve high activity and high yield. Patent documents 4 and 5 also provide improvement guidelines aimed at improving mechanical strength, and improve catalyst performance by preventing powdering during filling. Patent document 6 aims to improve the long-term stability of catalytic reactions by setting the standard deviation of catalyst particle size within a specific range. Patent document 7 proposes producing a catalyst that combines high catalytic performance and mechanical strength by controlling the relative centrifugal acceleration when molding using a tumbling granulator.

[0005] However, in the production of unsaturated carboxylic acids, improving the selectivity is an important issue. Improving the selectivity not only contributes to improving the yield, but also prevents reaction inhibition and runaway reactions caused by by-products, and is important for realizing stable operation over a long period of time. From the viewpoint of carbon neutrality, it is better to reduce by-products and obtain the target product in a high ratio, so technology for improving the selectivity is important. At present, there is no technology that can achieve sufficient selectivity, including those described in the above Patent Documents 1 to 7. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Publication No. 8-299797 [Patent Document 2] Japanese Patent Application Publication No. 2003-251184 [Patent Document 3] Japanese Patent Publication No. 2015-120133 [Patent Document 4] Japanese Patent Publication No. 2001-79408 [Patent Document 5] International Publication No. 2012 / 073584 [Patent Document 6] Japanese Patent Application Publication No. 2009-214105 [Patent Document 7] Japanese Patent Application Publication No. 2015-96497 Summary of the Invention [Problem to be solved by the invention]

[0007] In view of the above circumstances, an object of the present invention is to improve the selectivity in a process for producing corresponding unsaturated aldehydes and unsaturated carboxylic acids using propylene, isobutylene, t-butyl alcohol, etc. as raw materials, and in a gas-phase catalytic oxidation process for producing 1,3-butadiene from butenes. [Means for solving the problem]

[0008] As a result of extensive research into the current situation and problems described above, the inventors of the present application have found that specific catalyst shape parameters contribute to improving the selectivity, and have thus made the present invention.

[0009] That is, the present invention relates to the following 1) to 9). 1) A catalyst having a sphericity parameter SPHT3 value of 0.9822 or more, obtained by particle shape measurement using dynamic image analysis. Here, the sphericity parameter SPHT3 is a value obtained by the following formula (I): SPHT3 = 4πA ÷ P 2 (I) In the above formula (I), A is the area of ​​the particle photographed by dynamic image analysis, and P is the perimeter of the particle. 2) The catalyst according to the above 1), wherein the catalytically active component is represented by the following formula (1): (Mo) 12 (V) a (W) b (Cu) c (Sb) d (X) e (Y) f (Z) g (O) h (1) (In formula (1), Mo, V, W, Cu, Sb, and O represent molybdenum, vanadium, tungsten, copper, antimony, and oxygen, respectively; X represents at least one element selected from the group consisting of alkali metals and thallium; Y represents at least one element selected from the group consisting of magnesium, calcium, strontium, barium, and zinc; Z represents at least one element selected from the group consisting of niobium, cerium, tin, chromium, manganese, iron, cobalt, samarium, germanium, titanium, and arsenic. Also, a, b, c, d, e, f, g, and h represent the atomic ratios of the respective elements. With respect to 12 molybdenum atoms, a satisfies 0 < a ≤ 10.0, b satisfies 0 ≤ b ≤ 10.0, c satisfies 0 < c ≤ 6.0, d satisfies 0 ≤ d ≤ 10.0, e satisfies 0 ≤ e ≤ 0.50, f satisfies 0 ≤ f ≤ 1.0, and g satisfies 0 ≤ g < 6.0. Further, h is the number of oxygen atoms necessary to satisfy the valences of the respective components.) 3) The catalyst according to 2) above, wherein in the formula (1), 1.0 ≤ a ≤ 5.0, 0.50 ≤ b ≤ 3.0, 0.50 ≤ c ≤ 3.0, and 0 < d ≤ 2.0. 4) The catalyst according to 1) above, wherein the catalytic active component is represented by the following formula (2). Mo 12 Bi b1 Ni c1 Co d1 Fe e1 X f1 Y g1 Z h1 O i1 ···(2) (In the formula, Mo, Bi, Ni, Co, and Fe represent molybdenum, bismuth, nickel, cobalt, and iron respectively, X represents at least one element selected from tungsten, antimony, tin, zinc, chromium, manganese, magnesium, calcium, silicon, aluminum, cerium, and titanium, Y represents at least one element selected from sodium, potassium, cesium, rubidium, and thallium, Z belongs to Group 1 to Group 16 of the periodic table and means at least one element selected from elements other than the above Mo, Bi, Ni, Co, Fe, X, and Y, and b1, c1, d1, e1, f1, g1, h1, and i1 represent the number of atoms of molybdenum, bismuth, nickel, cobalt, iron, X, Y, Z, and oxygen respectively, satisfying 0 < b1 ≤ 7.0, 0 ≤ c1 ≤ 10.0, 0 < d1 ≤ 10.0, 0 < c1 + d1 ≤ 20.0, 0 < e1 ≤ 5.0, 0 ≤ f1 ≤ 2.0, 0 ≤ g1 ≤ 3.0, 0 ≤ h1 ≤ 5.0, and i1 is a value determined by the oxidation state of each element.) 5) The catalyst according to 4) above, wherein in the formula (2), 0.50 ≤ b1 ≤ 1.7, 1.0 ≤ c1 ≤ 3.3, 5.0 ≤ d1 ≤ 6.8, and 1.0 ≤ e1 ≤ 3.0. 6) The catalyst according to any one of 1) to 5) above, which is a catalyst in which a catalytic active component is supported on an inert carrier. 7) The catalyst according to 6) above, wherein the inert carrier is silica, alumina, or a combination thereof. 8) The catalyst according to any one of 1) to 7) above, which is for producing an unsaturated aldehyde, an unsaturated carboxylic acid, or a conjugated diene compound. 9) A method for producing an unsaturated aldehyde, an unsaturated carboxylic acid, or a conjugated diene compound using the catalyst according to any one of 1) to 8) above.

Advantages of the Invention

[0010] According to the present invention, in a method for producing corresponding unsaturated aldehydes or unsaturated carboxylic acids using propylene, isobutylene, t-butyl alcohol or the like as raw materials, or in a gas-phase catalytic oxidation method for producing 1,3-butadiene from butenes, high selectivity can be maintained. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a schematic diagram showing a method of adding a binder in Example 1. [Diagram 2] FIG. 2 is a schematic diagram showing a method of adding a binder in Example 2. [Diagram 3] FIG. 3 is a schematic diagram showing a method of adding a binder in Example 3. [Figure 4] FIG. 4 is a schematic diagram showing a method of adding a binder in Comparative Example 1. [Diagram 5] FIG. 5 is a schematic diagram showing a method of adding a binder in Comparative Example 2. [Figure 6] FIG. 6 is a schematic diagram showing a method of adding a binder in Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] [Particle shape by dynamic image analysis] The catalyst of the present invention has an SPHT3 (sphericity) value of 0.9822 or more, which is obtained by particle shape measurement using dynamic image analysis. Dynamic image analysis is a method of obtaining particle size distribution and shape distribution (aspect ratio, sphericity, etc.) by continuously photographing particles dispersed in a fluid (solvent, etc.) and performing measurement, binarization, and analysis. An example of a practical device for implementing dynamic image analysis is the CAMSIZER X2 (manufactured by Microtrack Bell). In this specification, sphericity and sphericity parameter (SPHT3) are synonymous. Sphericity SPHT3 is calculated by analyzing successively captured particle images, and applying the perimeter P of the captured image of each particle and the area A of each particle to the following formula (I). A perfect sphere has an SPHT3 of 1, and particles of all other shapes have an SPHT3 value less than 1 and greater than 0. SPHT3 = 4πA ÷ P 2 (I) In the present invention, when the SPHT3 value of a catalyst is within a certain range, it means that the average value of SPHT3 measured for about 100 to 200 particles of the catalyst is within the range. The lower limit of the SPHT3 is more preferably 0.9830, 0.9835, 0.9840, 0.9845, 0.9850, 0.9855, 0.9860, 0.9865, and particularly preferably 0.9870. The upper limit may be 1.0000, but is more preferably 0.9950, 0.9900, 0.9890, and particularly preferably 0.9880. Therefore, the range of SPHT3 is preferably 0.9830 or more and 1.0000 or less, more preferably 0.9835 or more and 1.0000 or less, more preferably 0.9840 or more and 1.0000 or less, more preferably 0.9845 or more and 1.0000 or less, more preferably 0.9850 or more and 1.0000 or less, more preferably 0.9855 or more and 0.9950 or less, more preferably 0.9860 or more and 0.9900 or less, more preferably 0.0.9865 or more and 0.9890 or less, and most preferably 0.9870 or more and 0.9880 or less.

[0013] The inventors of the present invention found that the closer the shape of the catalyst is to a perfect sphere (i.e., the larger the SPHT3 value), the higher the selectivity. This is thought to be because, when gas is passed through a reaction tube filled with the catalyst to carry out a catalytic reaction, the closer the shape of the catalyst is to a perfect sphere, the more the gas flows and flows without stagnation in the catalyst layer, reducing the contact time with the catalyst, resulting in an improvement in selectivity. Another factor is that the closer the shape of the catalyst is to a perfect sphere, the more uniform the pore distribution and / or the thickness of the active component of the spherical catalyst are, and the reaction proceeds without localized accumulation of reaction heat.

[0014] [Symm3 (Symmetry)] In the present invention, Symm3 is a parameter indicating geometric symmetry that is analyzed from images captured continuously by dynamic image analysis, and is calculated as follows. First, a straight line is drawn in any direction through the center of gravity of the image taken of each particle and intersecting with the outer periphery of the particle. The distances from the center of gravity to the outer periphery of the particle are defined as r1 and r2. When the direction of the straight line is changed, the smallest r1 / r2 is defined as min(r1 / r2), and the value calculated by applying it to the following formula (II) is defined as Symm3 (symmetry). In terms of selectivity, the catalyst of the present invention is more preferably one in which Symm3 (symmetry) is 0.9750 or more and 0.9865 or less. The lower limit of Symm3 is more preferably 0.9760, 0.9770, 0.9780, 0.9790, 0.9800, 0.9810, 0.9820, and particularly preferably 0.9825. The upper limit is more preferably 0.9861, 0.9855, 0.9845, and particularly preferably 0.9835. Therefore, the range of Symm3 is more preferably 0.9760 or more and 0.9865 or less, more preferably 0.9770 or more and 0.9865 or less, more preferably 0.9780 or more and 0.98650 or less, more preferably 0.9790 or more and 0.9865 or less, more preferably 0.9800 or more and 0.9861 or less, more preferably 0.9810 or more and 0.9855 or less, more preferably 0.9820 or more and 0.9845 or less, and most preferably 0.9825 or more and 0.9835 or less. Symm3={1+min(r1 / r2)} / 2 ···(II)

[0015] Aspect Ratio The aspect ratio b / I3 in the present invention is a parameter that indicates the shape of each particle continuously imaged by dynamic image analysis, and is calculated as follows: When an arbitrary point on the outer periphery of an imaged particle is designated as P, a straight line is drawn from point P through the inside of the particle so as to intersect with point Q on the outer periphery different from point P, and the maximum value of the length when point Q is moved along the outer periphery is defined as the cord diameter X. cThe cord diameter X measured when point P is moved along the circumference is c The minimum value of the minimum cord diameter x cmin Next, when two parallel tangents are drawn that sandwich each particle, the distance between the tangents is the Feret diameter X Fe The Feret diameter X when the tangent direction is changed Fe The maximum value of the maximum Feret diameter X FeMAX The aspect ratio b / I3 is calculated by the following formula (III). In terms of selectivity, the catalyst of the present invention is more preferably one in which the aspect ratio b / I3 is 0.9275 or more and 0.9580 or less. The lower limit of the aspect ratio is more preferably 0.9280, 0.9300, 0.9350, 0.9400, 0.9410, 0.9420, 0.9430, and particularly preferably 0.9440. The upper limit is more preferably 0.9542, 0.9540, 0.9530, 0.9525, 0.9520, 0.9500, 0.9475, and particularly preferably 0.9450. Therefore, the range of the aspect ratio is more preferably 0.9280 or more and 0.9542 or less, more preferably 0.9300 or more and 0.9540 or less, more preferably 0.9350 or more and 0.9530 or less, more preferably 0.9400 or more and 0.9525 or less, more preferably 0.9410 or more and 0.9520 or less, more preferably 0.9420 or more and 0.9500 or less, more preferably 0.9430 or more and 0.9475 or less, and most preferably 0.9440 or more and 0.9450 or less. b / I3=X cmin / X FeMAX (III)

[0016] [Catalyst composition for producing unsaturated carboxylic acid] When the catalyst of the present invention is used as a catalyst for producing an unsaturated carboxylic acid, it is preferable that the catalytically active component has a composition represented by the following formula (1). (Mo) 12 (V) a (W) b (Cu) c (Sb) d (X) e (Y) f (Z) g(O) h (1) (In the formula, Mo, V, W, Cu, Sb, and O represent molybdenum, vanadium, tungsten, copper, antimony, and oxygen, respectively; X represents at least one element selected from the group consisting of alkali metals and thallium; Y represents at least one element selected from the group consisting of magnesium, calcium, strontium, barium, and zinc; Z represents at least one element selected from the group consisting of bismuth, tellurium, silver, selenium, silicon, aluminum, boron, niobium, cerium, tin, chromium, manganese, iron, cobalt, nickel, samarium, germanium, zirconium, titanium, tantalum, lead, indium, sulfur, palladium, gallium, lanthanum, and arsenic. Also, a, b, c, d, e, f, g, and h represent the atomic ratios of the respective elements. With respect to 12 molybdenum atoms, a satisfies 0 < a ≤ 10.0, b satisfies 0 ≤ b ≤ 10.0, c satisfies 0 < c ≤ 6.0, d satisfies 0 ≤ d ≤ 10.0, e satisfies 0 ≤ e ≤ 0.50, f satisfies 0 ≤ f ≤ 1.0, and g satisfies 0 ≤ g < 6.0. Further, h is the number of oxygen atoms necessary to satisfy the valences of the respective components.)

[0017] In the above formula (1), the preferred ranges of a to g are as follows. The lower limits of a are, in order of preference, 0.20, 0.50, 0.80, 1.0, 1.5, 2.0, 2.2, 2.5, and most preferably 2.8. The upper limits of a are, in order of preference, 9.0, 8.0, 7.0, 6.0, 5.0, 4.5, 4.0, 3.5, and most preferably 3.2. That is, as the range of a, 0.20 ≤ a ≤ 9.0 is preferred, 0.50 ≤ a ≤ 8.0 is more preferred, 0.80 ≤ a ≤ 7.0 is more preferred, 1.0 ≤ a ≤ 6.0 is more preferred, 1.5 ≤ a ≤ 5.0 is more preferred, 2.0 ≤ a ≤ 4.5 is more preferred, 2.2 ≤ a ≤ 4.0 is more preferred, 2.5 ≤ a ≤ 3.5 is more preferred, and most preferably, 2.8 ≤ a ≤ 3.2. The lower limit of b is, in order of desirability, 0.10, 0.20, 0.30, 0.40, 0.50, 0.60, 0.70, 0.80, 0.90, and most desirably 1.0, and the upper limit of b is, in order of desirability, 9.0, 8.0, 7.0, 6.0, 5.0, 4.0, 3.0, 2.5, 2.0, 1.5, and most desirably 1.4. That is, the range of b is preferably 0.10≦b≦9.0, more preferably 0.10≦b≦8.0, more preferably 0.20≦b≦7.0, more preferably 0.30≦b≦6.0, more preferably 0.40≦b≦5.0, more preferably 0.50≦b≦4.0, more preferably 0.60≦b≦3.0, more preferably 0.70≦b≦2.5, more preferably 0.80≦b≦2.0, more preferably 0.90≦b≦1.5, and most preferably 1.0≦b≦1.4. The lower limit of c is, in order of desirability, 0.10, 0.20, 0.30, 0.40, 0.50, 0.60, 0.70, 0.80, 0.90, and most desirably 1.0, and the upper limit of c is, in order of desirability, 5.0, 4.0, 3.0, 2.5, 2.0, 1.5, and most desirably 1.4. That is, the range of c is preferably 0.10≦c≦5.0, more preferably 0.20≦c≦5.0, more preferably 0.30≦c≦5.0, more preferably 0.40≦c≦5.0, more preferably 0.50≦c≦4.0, more preferably 0.60≦c≦3.0, more preferably 0.70≦c≦2.5, more preferably 0.80≦c≦2.0, more preferably 0.90≦c≦1.5, and most preferably 1.0≦c≦1.4. The lower limit of d is, in order of desirability, 0.11, 0.15, 0.18, 0.20, 0.25, 0.30, and 0.35, and is most desirably 0.40, and the upper limit of d is, in order of desirability, 9.0, 8.0, 7.0, 6.0, 5.0, 4.0, 3.0, 2.5, 2.0, 1.5, and 1.0, and is most desirably 0.70. That is, the range of d is preferably 0.11≦d≦9.0, more preferably 0.11≦d≦8.0, more preferably 0.11≦d≦7.0, more preferably 0.11≦d≦6.0, more preferably 0.11≦d≦5.0, more preferably 0.15≦d≦4.0, more preferably 0.18≦d≦3.0, more preferably 0.20≦d≦2.5, more preferably 0.25≦d≦2.0, more preferably 0.30≦d≦1.5, more preferably 0.35≦d≦1.0, and most preferably 0.40≦d≦0.70. The upper limit of e is, in order of desirability, 0.40, 0.30, 0.20, and 0.10. That is, the most preferable range of e is 0≦e≦0.10. The upper limit of f is, in order of desirability, 0.80, 0.50, 0.20, 0.15, and most desirably 0.10. That is, the most preferable range of f is 0≦g1≦0.10. The upper limit of g is, in order of desirability, 5.0, 4.0, 3.0, 2.0, 1.0, 0.050, 0.025, and 0.015. That is, the most preferable range of g is 0≦g≦0.015.

[0018] [About support] A catalyst in which the catalytically active component is preliminarily calcined after preparation and the preliminarily calcined powder is supported on an inert carrier is particularly effective. The inert carrier may be made of known materials such as alumina, silica, titania, zirconia, niobia, silica alumina, silicon carbide, carbides, and mixtures thereof. There are no particular limitations on the particle size, water absorption rate, mechanical strength, crystallinity of each crystal phase, or mixing ratio of the inert carrier, and appropriate ranges should be selected taking into consideration the final catalyst performance, moldability, production efficiency, etc. The mixing ratio of the carrier and the pre-calcined powder is generally calculated as the loading rate using the following formula based on the charged mass of each raw material. In addition, if it is clear that additives such as molding aids and strength improvers remain in the catalyst after the main calcination, they are included in the total amount (denominator). Loading rate (mass%) = (mass of pre-calcined powder used for molding) / {(mass of pre-calcined powder used for molding) + (mass of support used for molding)} x 100 The upper limit of the above-mentioned loading rate is preferably 80% by mass, and more preferably 60% by mass. The lower limit is preferably 20% by mass, and more preferably 30% by mass. That is, the loading rate is preferably from 20% by mass to 80% by mass, and most preferably from 30% by mass to 60% by mass. As the inert carrier, silica and / or alumina are preferred, and a mixture of silica and alumina is particularly preferred. In addition, it is preferable to use a binder when supporting. Specific examples of binders that can be used include water, ethanol, methanol, propanol, polyhydric alcohols, polyvinyl alcohol as a polymer binder, and silica sol aqueous solution as an inorganic binder. Ethanol, methanol, propanol, and polyhydric alcohols are preferable, diols such as ethylene glycol and triols such as glycerin are preferable, and an aqueous solution of glycerin with a concentration of 5% by mass or more is preferable. By using an appropriate amount of an aqueous glycerin solution, moldability is improved, and a high-performance catalyst with high mechanical strength can be obtained. The amount of these binders used is usually 2 to 60 parts by mass relative to 100 parts by mass of the pre-calcined powder, but in the case of an aqueous glycerin solution, 10 to 30 parts by mass is preferable. When supporting, the binder and the pre-calcined powder may be supplied alternately or simultaneously to the molding machine.

[0019] The supported catalyst obtained as described above can be directly used as a catalyst in a gas-phase catalytic oxidation reaction, but calcination is preferable because it may improve the catalytic activity. The calcination method and conditions are not particularly limited, and known treatment methods and conditions can be applied. The optimal conditions for calcination vary depending on the catalyst raw material used, catalyst composition, preparation method, etc., but the calcination temperature is usually 100 to 450°C, preferably 270 to 420°C, and particularly preferably 350 to 390°C, and the calcination time is 1 to 20 hours. The calcination is usually performed in an air atmosphere, but may be performed in an inert gas atmosphere such as nitrogen, carbon dioxide, helium, or argon, or may be further calcined in an air atmosphere after calcination in an inert gas atmosphere as necessary.

[0020] When the catalyst of the present invention is used in a reaction for producing a corresponding unsaturated carboxylic acid from an unsaturated aldehyde such as acrolein or methacrolein as a raw material, particularly in a reaction for producing acrylic acid by gas-phase catalytic oxidation of acrolein with molecular oxygen or a molecular oxygen-containing gas, it is possible to improve the catalytic activity and reduce the differential pressure, which is very effective compared to known methods. In addition, in a process of partial oxidation reaction accompanied by heat generation, it is expected to have an effect of improving stability by reducing hot spot temperature, etc. Furthermore, the catalyst of the present invention is also effective in reducing by-products that adversely affect the environment and the quality of the final product, such as carbon monoxide (CO), carbon dioxide (CO2), acetaldehyde, acetic acid, and formaldehyde.

[0021] In the method for producing an unsaturated carboxylic acid of the present invention, the method for flowing the raw material gas may be a normal single flow method or a recycle method, and may be carried out under generally used conditions and is not particularly limited. For example, a mixed gas consisting of 1 to 10 volume %, preferably 4 to 9 volume %, of unsaturated aldehyde as a starting raw material substance at room temperature, 3 to 20 volume %, preferably 4 to 18 volume %, of molecular oxygen, 0 to 60 volume %, preferably 4 to 50 volume %, of water vapor, and 20 to 80 volume %, preferably 30 to 60 volume %, of an inert gas such as carbon dioxide or nitrogen, is filled in a reaction tube and then, at 240 to 450°C, under a pressure of normal pressure to 10 atm, at a space velocity of 300 to 5000 h-1 and the reaction is carried out.

[0022] [About inorganic fibers] The catalyst of the present invention preferably contains inorganic fibers for the purpose of improving mechanical strength, etc. The material of the inorganic fibers is not particularly limited, and for example, glass fibers (glass fibers), ceramic fibers, metal fibers, mineral fibers, carbon fibers, various whiskers, etc. can be used. Among these, glass fibers treated with silane-based chemicals are particularly preferred. The fiber length is not particularly limited as long as it does not impair the effects of the present invention, but the average fiber length is preferably about 1 to 1000 μm, more preferably about 10 to 500 μm. Furthermore, two or more kinds of inorganic fibers can be used in combination. Two or more kinds of fibers may be made of different materials, or two kinds of fibers made of the same material but with different average fiber lengths.

[0023] [Method of producing catalyst for producing unsaturated carboxylic acid] A specific example of the process for obtaining the catalyst for producing an unsaturated carboxylic acid of the present invention will be described below. Step a) Mixing Generally, when ammonium molybdate is used as the raw material for each element constituting the catalyst, a high performance catalyst can be obtained. As the raw materials of tungsten, vanadium, antimony, copper and other elements, oxides or ammonium salts, carbonates, organic acid salts, hydroxides, etc. that can be converted to oxides by ignition, or mixtures thereof can be used. For example, vanadium component raw material, molybdenum component raw material, and antimony component raw material are mixed in a desired ratio with a separately prepared aqueous solution or slurry of tungsten component raw material and Z component raw material under conditions of 20 to 95 ° C., and heated and stirred for about 1 hour under conditions of 20 to 90 ° C., and then an aqueous solution in which a copper component raw material is dissolved and, if necessary, an X component raw material and a Y component raw material are added to obtain an aqueous solution or slurry containing a catalyst component. Hereinafter, the aqueous solution or slurry obtained in this way is collectively referred to as the prepared liquid (A). Here, the prepared liquid (A) does not necessarily need to contain all the catalyst constituent elements, and some of the elements or some of the amounts of the elements may be added in a subsequent step. Furthermore, when preparing the preparation liquid (A), if the amount of water in which each component raw material is dissolved, or if an acid such as sulfuric acid, nitric acid, hydrochloric acid, tartaric acid, or acetic acid is added for dissolution, is not appropriate within the range of, for example, 5% by mass to 99% by mass, the aqueous solution must have an acid concentration sufficient to dissolve the raw materials; otherwise, the preparation liquid (A) may take the form of a clay-like mass, which will not serve as an excellent catalyst. Therefore, the preparation liquid (A) obtained is preferably in the form of an aqueous solution or a slurry, in order to obtain an excellent catalyst.

[0024] Step b) Drying Next, the prepared liquid (A) obtained above is dried to obtain a dry powder. The drying method is not particularly limited as long as it can completely dry the prepared liquid (A), and examples thereof include drum drying, freeze drying, spray drying, and evaporation to dryness. Among these, in the present invention, spray drying is particularly preferred, which can dry the slurry into powder or granules in a short time. The drying temperature of the spray drying varies depending on the concentration of the slurry, the liquid sending speed, etc., but is generally 70 to 150°C at the outlet of the dryer. In addition, it is preferable to dry the mixture so that the average particle size of the dry powder obtained at this time is 20 to 700 μm. In this way, a dry powder (B) is obtained.

[0025] Step c) Pre-firing The resulting dry powder (B) is calcined under air flow at 200°C to 500°C, preferably 300°C to 400°C, which tends to improve the moldability, mechanical strength, and catalytic performance of the catalyst. The calcination time is preferably 1 hour to 12 hours. In this way, a pre-calcined body (C) is obtained.

[0026] Step d) Crushing The obtained pre-calcined body (C) is obtained as a solid (D) in which the dry powder (B) is aggregated by pre-calcination. In order to obtain the pre-calcined powder (E) required in the next molding step, the solid (D) is pulverized. The pulverization method is not particularly limited, and examples thereof include a roller mill, a jet mill, a hammer mill, a rotary mill, and a vibration mill. The average particle size (pre-calcined median size) of the pre-calcined powder (E) obtained at this time is preferably 10 μm or more and 100 μm or less, more preferably 20 μm or more and 80 μm or less, even more preferably 30 μm or more and 50 μm or less, and particularly preferably 35 μm or more and 45 μm or less. In the present specification, the crushed pre-calcined powder (E) is described as a catalyst precursor. However, in the case where there is no agglomeration at the pre-calcined body (C) stage and it can be used without going through a crushing step, the pre-calcined body (C) may be used as a catalyst precursor.

[0027] Process e) Molding There is no particular limitation on the molding method, but it is preferable to mold the pre-calcined powder (E) into a spherical shape. The pre-calcined powder (E) may be molded into a spherical shape using a molding machine, but a method in which the pre-calcined powder (E) (including a molding aid and a strength improver, if necessary) is supported on a carrier such as an inactive ceramic is preferable. Here, the supporting method is widely known to include a rolling granulation method, a method using a centrifugal fluidized coating device, a wash coat method, etc., and is not particularly limited as long as the pre-calcined powder (E) can be uniformly supported on the carrier. However, in consideration of the production efficiency of the catalyst and the performance of the prepared catalyst, it is more preferable to use an apparatus having a flat or uneven disk at the bottom of a fixed cylindrical container, which rotates the disk at high speed to vigorously stir the carrier charged in the container by the rotation and revolution of the carrier itself, and the pre-calcined powder (E) and, if necessary, a molding aid and / or a strength improver and a pore former are added thereto to support the powder components on the carrier. In addition, it is preferable to use a binder for the support. Specific examples of binders that can be used include water, ethanol, methanol, propanol, polyhydric alcohols, polyvinyl alcohol as a polymer binder, and silica sol aqueous solution as an inorganic binder. Ethanol, methanol, propanol, and polyhydric alcohols are preferred, and diols such as ethylene glycol and triols such as glycerin are more preferred. By using an appropriate amount of glycerin aqueous solution, moldability is improved and a high-performance catalyst with high mechanical strength can be obtained. Specifically, a particularly high-performance catalyst can be obtained when an aqueous solution of glycerin with a concentration of 5% by mass or more is used. The amount of these binders used is usually 2 to 80 parts by mass per 100 parts by mass of the pre-calcined powder (E). An inert carrier of about 2 to 8 mm is usually used, and the pre-calcined powder (E) is supported on it. The support rate is determined in consideration of the catalyst use conditions, such as the space velocity of the reaction raw materials and the raw material concentration, and is usually 20% by mass to 80% by mass. Here, the loading rate is expressed as in the following formula (4) when a molding aid or strength improver, etc., is used in molding. In this way, a molded body (F) is obtained. In addition, the present inventors have found that the present invention is difficult to maintain mechanical strength. Therefore, it is preferable to add inactive inorganic fibers as a strength improver during support molding, and glass fibers are particularly preferable. When fibers are used as a strength improver, the amount of these fibers used is usually 1 to 30 parts by mass, preferably 2 to 10 parts by mass, and more preferably 3 to 5 parts by mass, per 100 parts by mass of the catalytically active component solid. The inert carrier may be made of known materials such as alumina, silica, titania, zirconia, niobia, silica alumina, silicon carbide, carbides, and mixtures thereof. There are no particular limitations on the particle size, water absorption rate, mechanical strength, crystallinity of each crystal phase, or mixture ratio of the inert carrier, and appropriate ranges should be selected in consideration of the final catalyst performance, moldability, production efficiency, etc.

[0028] [Formula (4)] Loading rate (mass%) = 100 × [mass of pre-calcined powder (E) used for molding / (mass of pre-calcined powder (E) used for molding + mass of inert carrier used for molding)] In addition, when it is clear that additives such as molding aids and strength improvers remain in the catalyst after main calcination, they are included in the total amount (denominator).

[0029] Step f) Main firing The molded body (F) tends to have improved catalytic activity and effective yield by calcining it at a temperature of 100 to 450°C for about 1 to 12 hours. The calcination temperature is preferably 270°C to 420°C, more preferably 350°C to 400°C. Air is the preferred gas to be circulated because it is simple, but other inert gases such as nitrogen, carbon dioxide, nitrogen oxide-containing gas for creating a reducing atmosphere, ammonia-containing gas, hydrogen gas, and mixtures thereof can also be used. In this way, the catalyst (G) is obtained.

[0030] [How to adjust SPHT3] The value of the above-mentioned SPHT3 can be adjusted by changing the raw materials used in the above step a), the spray-drying conditions in the above step b), the firing temperature and time in the above step c), the pulverization method and the median diameter after pulverization in the above step d), the relative centrifugal acceleration, the loading rate, the type of binder, the addition position of the binder, etc. in the above step e). However, it is difficult to significantly change it by changing a single condition alone, and it can be achieved by optimizing two or more conditions. Several examples are shown below.

[0031] <Firing temperature and time in step c)> As described above, the firing temperature is preferably 200°C to 500°C, but when it is increased, SPHT3 tends to increase. Therefore, for adjusting SPHT3, it is preferably 380°C or higher. Also, since SPHT3 can increase when the firing time is lengthened, it is preferably 3 hours or more. <Pulverization method and median diameter in step d)> SPHT3 can also be controlled by the method in step d). When using a ball mill, it is easy to adjust SPHT3, and SPHT3 can also be adjusted by setting the median diameter of the pre-fired body (c) within a certain range. <Relative centrifugal acceleration and loading rate in step e)> The value of SPHT3 can also be adjusted by changing the relative centrifugal acceleration in step e). The relative centrifugal acceleration may be about 2.0G or more and 30G or less. However, when it is increased, SPHT3 tends to increase, and it is most optimal to be about 8.0 or more and 12.0 or less. However, it also varies depending on the quantitative relationship (loading rate) between the carrier and the pre-fired powder supported thereon. <Median diameter in step d) and addition position of binder in step e)> SPHT3 can also be controlled by setting the median diameter of the pre-fired powder within a certain range by the method in step d), and SPHT3 can also be adjusted by changing the addition position of the binder in step e). The binder is preferably added at a position away from the addition position of the granules. Multiple addition ports may be provided, but the more addition ports there are, the easier it is for SPHT3 to decrease. Therefore, it is preferably 2 or less addition ports.

[0032] The above method for adjusting SPHT3 also applies to the adjustment of Symm3 and the aspect ratio. That is, Symm3 and the aspect ratio can be adjusted by changing two or more of the conditions a) to f).

[0033] [Catalyst composition for producing unsaturated aldehyde or conjugated diene compound] When the catalyst of the present invention is used as a catalyst for producing an unsaturated aldehyde or a conjugated diene compound, the catalytic active component preferably has a composition represented by the following formula (2). Mo 12 Bi b1 Ni c1 Co d1 Fe e1 X f1 Y g1 Z h1 O i1 ···(2) (In the formula, Mo, Bi, Ni, Co, and Fe represent molybdenum, bismuth, nickel, cobalt, and iron respectively, X represents at least one element selected from tungsten, antimony, tin, zinc, chromium, manganese, magnesium, calcium, silicon, aluminum, cerium, and titanium, Y represents at least one element selected from sodium, potassium, cesium, rubidium, and thallium, Z belongs to Groups 1 to 16 of the periodic table and means at least one element selected from elements other than the above Mo, Bi, Ni, Co, Fe, X, and Y, and b1, c1, d1, e1, f1, g1, h1, and i1 represent the number of atoms of molybdenum, bismuth, nickel, cobalt, iron, X, Y, Z, and oxygen respectively, satisfying 0 < b1 ≦ 7, 0 ≦ c1 ≦ 10, 0 < d1 ≦ 10, 0 < c1 + d1 ≦ 20, 0 < e1 ≦ 5, 0 ≦ f1 ≦ 2, 0 ≦ g1 ≦ 3, 0 ≦ h1 ≦ 5, and i1 is a value determined by the oxidation state of each element.)

[0034] In the above formula (2), the preferable ranges of b1 to h1 are as follows. The lower limit of b1 is preferably 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, and 0.7, and the upper limit is preferably 6.0, 5.0, 4.0, 3.0, 2.0, 1.8, 1.5, 1.2, and 1.0. That is, the range of b1 is preferably 0.1 or more and 6.0 or less, more preferably 0.1 or more and 5.0 or less, more preferably 0.1 or more and 4.0 or less, more preferably 0.2 or more and 3.0 or less, more preferably 0.3 or more and 2.0 or less, more preferably 0.4 or more and 1.8 or less, more preferably 0.5 or more and 1.5 or less, more preferably 0.6 or more and 1.2 or less, and most preferably 0.7 or more and 1.0 or less. The lower limit of c1 is preferably 0.2, 0.5, 0.8, 1.0, 1.5, and 1.7, and the upper limit is preferably 8.0, 7.0, 6.0, 5.0, 4.0, 3.5, 3.3, and 3.0. That is, the range of c1 is preferably 0.2 or more and 8.0 or less, more preferably 0.2 or more and 7.0 or less, more preferably 0.2 or more and 6.0 or less, more preferably 0.2 or more and 5.0 or less, more preferably 0.2 or more and 4.0 or less, more preferably 0.5 or more and 3.5 or less, more preferably 0.8 or more and 3.3 or less, more preferably 1.0 or more and 3.0 or less, more preferably 1.5 or more and 2.7 or less, and most preferably 1.7 or more and 3.0 or less. The lower limit of d1 is preferably 1.0, 2.0, 3.0, 4.0, 5.0, 5.5, and 5.8, and the upper limit is preferably 9.5, 9.0, 8.5, 8.0, 7.5, 7.0, 6.8, and 6.6. That is, the range of d1 is preferably 1.0 to 9.5, more preferably 1.0 to 9.0, more preferably 2.0 to 8.5, more preferably 4.0 to 8.0, more preferably 5.0 to 7.0, more preferably 5.5 to 6.8, and most preferably 5.8 to 6.6. The lower limit of c1+d1 is preferably 1.2, 2.0, 4.0, 6.0, 8.0, and 8.3, and the upper limit is preferably 20.0, 15.0, 12.5, 11.0, 10.0, and 9.0. That is, the range of c1+d1 is preferably 1.2 or more and 20.0 or less, more preferably 2.0 or more and 15.0 or less, more preferably 4.0 or more and 12.5 or less, more preferably 6.0 or more and 11.0 or less, more preferably 8.0 or more and 10.0 or less, and most preferably 8.3 or more and 9.0 or less. The lower limit of e1 is preferably 0.1, 0.2, 0.5, 0.8, 1.0, 1.5, and 1.6, and the upper limit is preferably 4.5, 4.0, 3.5, 3.0, 2.5, and 2.3. That is, the range of e1 is preferably 0.1 to 4.5, more preferably 0.2 to 4.5, more preferably 0.5 to 3.5, more preferably 0.8 to 3.0, more preferably 1.0 to 2.5, more preferably 1.5 to 2.5, and most preferably 1.6 to 2.3. The upper limit of f1 is preferably 1.8, 1.5, 1.0, 0.8, and 0.5, and the lower limit is preferably 0. That is, the range of f1 is preferably 0 or more and 1.8 or less, 0 or more and 1.5 or less, 0 or more and 1.0 or less, 0 or more and 0.8 or less, and 0 or more and 0.5 or less, and most preferably f1 is 0. The lower limit of g1 is preferably 0.010, 0.020, and 0.030, and the upper limit is preferably 2, 1, 0.5, 0.4, 0.3, 0.2, 0.15, and 0.10. That is, the range of g1 is preferably 0.010 or more and 2 or less, more preferably 0.010 or more and 1 or less, more preferably 0.010 or more and 0.5 or less, more preferably 0.010 or more and 0.4 or less, more preferably 0.010 or more and 0.3 or less, more preferably 0.010 or more and 0.2 or less, more preferably 0.020 or more and 0.15 or less, and the most preferable range is 0.030 or more and 0.10 or less. The upper limit of h1 is preferably 4.0, 3.0, 2.0, 1.8, 1.5, 1.0, 0.8, and 0.5, and the lower limit is preferably 0. That is, the range of h1 is preferably 0 or more and 4.0 or less, 0 or more and 3.0 or less, 0 or more and 2.0 or less, 0 or more and 1.8 or less, 0 or more and 1.5 or less, 0 or more and 1.0 or less, 0 or more and 0.8 or less, and 0 or more and 0.5 or less, and most preferably h1 is 0.

[0035] In the formula (2), X is preferably tungsten, antimony, zinc, magnesium, calcium or cerium. In the formula (2), Y is preferably sodium, potassium or cesium, more preferably potassium or cesium. In the formula (2), Z is preferably vanadium, copper, niobium, zirconium, calcium, beryllium, strontium, barium, lead, or phosphorus.

[0036] [Method of producing catalysts for producing unsaturated aldehydes and conjugated diene compounds] The starting materials for the elements constituting the catalyst represented by the above formula (2) are not particularly limited. For example, as the starting material for the molybdenum component, there can be used molybdenum oxides such as molybdenum trioxide, molybdic acid, ammonium paramolybdate, ammonium metamolybdate, or a salt thereof, a molybdenum-containing heteropolyacid such as phosphomolybdic acid, silicomolybdic acid, or a salt thereof, and the like.

[0037] The raw material for the bismuth component can be bismuth salts such as bismuth nitrate, bismuth carbonate, bismuth sulfate, and bismuth acetate, bismuth trioxide, metallic bismuth, etc. These raw materials can be used as solids, or as an aqueous solution, a nitric acid solution, or a slurry of the bismuth compound produced from these aqueous solutions, but it is preferable to use the nitrate, or a solution thereof, or a slurry produced from the solution.

[0038] As the starting materials for the other component elements, ammonium salts, nitrates, nitrites, carbonates, subcarbonates, acetates, chlorides, inorganic acids, salts of inorganic acids, heteropolyacids, salts of heteropolyacids, sulfates, hydroxides, organic acid salts, oxides, or mixtures thereof of the metal elements generally used in this type of catalyst may be used in combination, with ammonium salts and nitrates being preferred.

[0039] These active ingredient-containing compounds may be used alone or in combination of two or more. The slurry liquid can be obtained by uniformly mixing each active ingredient-containing compound with water. The amount of water used in the slurry liquid is not particularly limited as long as it can completely dissolve all of the compounds used or can be uniformly mixed. The amount of water used can be appropriately determined taking into account the drying method and drying conditions. Usually, the amount of water used is 100 parts by mass or more and 2000 parts by mass or less with respect to 100 parts by mass of the total mass of the compounds for preparing the slurry. The amount of water is preferably large, but if it is too large, the energy cost of the drying process will be high and there is a risk that complete drying will not be possible.

[0040] The slurry of the source compounds of the above-mentioned component elements is preferably prepared by (i) mixing the above-mentioned source compounds all at once, (ii) mixing them all at once and then aging them, (iii) mixing them stepwise, (iv) repeating mixing and aging them stepwise, or a combination of (i) to (iv). Here, the aging refers to "processing an industrial raw material or semi-finished product under specific conditions such as a certain time and a certain temperature to obtain or increase the required physical or chemical properties or to advance a predetermined reaction." In the present invention, the above-mentioned certain time refers to a range of 5 minutes to 24 hours, and the above-mentioned certain temperature refers to a range above room temperature and below the boiling point of the aqueous solution or aqueous dispersion. Among these, the method (iii) of mixing stepwise is preferable in terms of the activity and yield of the finally obtained catalyst, and the more preferable method is a method in which each raw material to be mixed stepwise into the mother liquor is a solution in which it is completely dissolved, and the most preferable method is a method in which an alkali metal solution and various mixed solutions of nitrates are mixed into a mother liquor in which a molybdenum raw material is prepared as a mixed liquid or slurry. However, it is not always necessary to mix all of the catalyst constituent elements in this step, and some of the elements or some amounts of the elements may be added in a subsequent step.

[0041] In the present invention, the shape of the stirring blades of the stirrer used when mixing the essential active ingredients is not particularly limited, and any stirring blade such as a propeller blade, turbine blade, paddle blade, inclined paddle blade, screw blade, anchor blade, ribbon blade, large lattice blade, etc. can be used in one stage or in two or more stages of the same or different blades in the vertical direction. In addition, a baffle (baffle plate) may be installed in the reaction tank as necessary.

[0042] The slurry thus obtained is then dried. There are no particular limitations on the drying method as long as the slurry can be completely dried, and examples of the drying method include drum drying, freeze drying, spray drying, and evaporation to dryness. Among these, spray drying is particularly preferred in the present invention, as it can dry the slurry into powder or granules in a short time. The drying temperature for spray drying varies depending on the concentration of the slurry, the liquid delivery speed, etc., but generally the temperature at the outlet of the dryer is 70°C or higher and 150°C or lower.

[0043] The catalyst precursor obtained as described above is pre-calcined, molded, and then calcined, which makes it possible to control and maintain the molded shape, and thus produces a catalyst having excellent mechanical strength, particularly for industrial applications, and capable of exhibiting stable catalytic performance.

[0044] The molding can be performed by either of the molding methods of supported molding in which the catalyst is supported on an inert carrier such as silica, or non-supported molding in which no carrier is used. Specific molding methods include, for example, granulation molding. The shape of the molded product can be appropriately selected from, for example, spherical carriers, ellipsoidal carriers, etc., but it is preferable that the catalyst precursor is supported on an inert carrier such as a spherical carrier, particularly silica or alumina, and has an average particle size of 3.0 mm to 10.0 mm, preferably 3.0 mm to 8.0 mm. As the supporting method, a rolling granulation method, a method using a centrifugal fluidized coating device, a wash coat method, etc. are widely known, and are not particularly limited as long as the pre-calcined powder can be uniformly supported on the carrier, but the rolling granulation method is preferable when considering the production efficiency of the catalyst, etc. Specifically, the method is a method in which a carrier charged in a fixed cylindrical container is vigorously stirred by repeatedly rotating and revolving the carrier itself by using an apparatus having a flat or uneven disk at the bottom of the container, and the carrier is supported on the carrier by adding the pre-calcined powder to the container. It is preferable to use a binder for the support. Specific examples of binders that can be used include water, ethanol, methanol, propanol, polyhydric alcohols, polyvinyl alcohol as a polymer binder, and silica sol aqueous solutions as inorganic binders. Ethanol, methanol, propanol, and polyhydric alcohols are preferable, and diols such as ethylene glycol and triols such as glycerin are more preferable, and an aqueous solution of glycerin with a concentration of 5% by mass or more is even more preferable. By using an appropriate amount of an aqueous glycerin solution, the moldability is improved, and a high-performance catalyst with high mechanical strength can be obtained. The amount of these binders used is usually 2 to 60 parts by mass per 100 parts by mass of the pre-calcined powder, but in the case of a glycerin aqueous solution, 15 to 50 parts by mass is preferred. When supporting, the binder and the pre-calcined powder may be fed alternately or simultaneously to the molding machine. Also, during molding, a small amount of known additives, such as graphite, talc, etc., may be added. Note that the molding aids, pore-forming agents, and carriers added during molding are not considered as constituent elements of the active component in the present invention, regardless of whether they have activity in the sense of converting the raw material into some other product.

[0045] The pre-calcination method and pre-calcination conditions, or the main calcination method and main calcination conditions are not particularly limited, and known treatment methods and conditions can be applied. Pre-calcination and main calcination are usually performed under an oxygen-containing gas such as air or an inert gas flow at 200°C to 600°C, preferably 300°C to 550°C, for 0.5 hours or more, preferably 1 hour to 40 hours. Here, the inert gas refers to a gas that does not reduce the reaction activity of the catalyst, and specific examples include nitrogen, carbon dioxide, helium, and argon. In addition, the optimal conditions in the main calcination differ depending on the reaction conditions when producing unsaturated aldehydes and / or unsaturated carboxylic acids using a catalyst, and it is known to those skilled in the art to change the process parameters of the main calcination process, i.e., the oxygen content in the atmosphere, the maximum temperature reached, the calcination time, etc., and therefore are within the scope of the present invention. The calcination step is carried out after the pre-calcination step, and the maximum temperature reached in the calcination step (calcination temperature) is higher than the maximum temperature reached in the pre-calcination step (pre-calcination temperature). There are no particular limitations on the calcination method, such as a fluidized bed, a rotary kiln, a muffle furnace, or a tunnel calcination furnace, and the method should be appropriately selected taking into consideration the performance, mechanical strength, moldability, production efficiency, and other factors of the final catalyst.

[0046] The SPHT3, Symm3, and aspect ratio of the catalyst for producing an unsaturated aldehyde or conjugated diene compound can be adjusted by appropriately adjusting two or more of the conditions for preparation, drying, pre-calcination, pulverization, molding, and main calcination, in the same manner as the catalyst for producing an unsaturated carboxylic acid.

[0047] The catalyst of the present invention is preferably used as a catalyst for producing an unsaturated aldehyde compound, an unsaturated carboxylic acid compound, or a conjugated diene compound, and is preferably used according to its composition as described above. Specifically, the catalyst having the composition of the above formula (1) is particularly useful as a catalyst for producing an unsaturated carboxylic acid using an unsaturated aldehyde as a starting material. The catalyst having the composition of the above formula (2) is particularly useful as a catalyst for producing an unsaturated aldehyde using propylene, isobutylene, t-butyl alcohol, or the like as a starting material, or a conjugated diolefin using a monoolefin starting material as a starting material. In an exothermic reaction process such as producing an unsaturated aldehyde compound, an unsaturated carboxylic acid compound, or a conjugated diene compound, in an actual plant, in order to prevent the catalyst itself from being deteriorated by the heat generated by the reaction, different catalyst types may be packed in multiple layers so that the activity increases from the inlet side of the reaction tube to the outlet side of the reaction tube.

[0048] [Catalyst uses, etc.] In the method for producing acrolein or acrylic acid using the catalyst of the present invention, the method for flowing the raw material gas may be a normal single flow method or a recycle method, and may be carried out under generally used conditions and is not particularly limited. For example, a mixed gas consisting of 1 to 10% by volume, preferably 4 to 9% by volume of starting raw materials at room temperature, 3 to 20% by volume, preferably 4 to 18% by volume of molecular oxygen, 0 to 60% by volume, preferably 4 to 50% by volume of water vapor, and 20 to 80% by volume, preferably 30 to 60% by volume of inert gas such as carbon dioxide or nitrogen is filled in a reaction tube and then passed over the catalyst of the present invention at 240 to 450° C. under a pressure of normal pressure to 10 atm at a space velocity of 300 to 5000 h 2 . -1 and the reaction is carried out. In the above-mentioned method for producing acrolein or acrylic acid, it is preferable to use a multi-layer packing using different kinds of catalysts. That is, a catalyst layer formed by dividing into multiple n parts in the raw material gas flow direction of the reaction tube is provided, and the above-mentioned multiple kinds of catalysts are arranged so that the activity becomes higher from the raw material inlet to the outlet in the raw material gas flow direction. There is no particular limit to the number of divisions n, but it is usually 2 to 5, preferably 2 to 3. The above-mentioned different kinds of catalysts do not only mean the case where the catalyst composition is different, but also include the case where the support rate on the inert carrier is different or the case where the dilution rate is different. EXAMPLES

[0049] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples without departing from the spirit of the present invention. In the examples, the raw material conversion, yield, and selectivity were calculated according to the following formulas. Raw material conversion rate (%) = (number of moles of reacted acrolein) / (number of moles of supplied acrolein) × 100 Yield (%) = (moles of acrylic acid produced) / (moles of acrolein fed) x 100 Selectivity (%) = (moles of acrylic acid produced) / (moles of acrolein reacted) x 100

[0050] The median diameter of the pre-calcined powder shown in this example is the volume-based median value when the equivalent circle diameter Xarea of ​​the powder dispersed in air is measured using a Microtrack Bell CAMSIZER X2. area can be calculated from the following formula (IV) when the measured particle area is A. X area =(4A / π) (1 / 2) (IV)

[0051] [Example 1] <Production of Catalyst 1> 148 parts by mass of ammonium paratungstate was completely dissolved in 5241 parts by mass of pure water heated to 95 ° C. While stirring this solution, 166 parts by mass of ammonium metavanadate and 1000 parts by mass of ammonium molybdate were added, and after confirming dissolution, 70.5 parts by mass of antimony acetate was gradually added and thoroughly stirred. Next, 143 parts by mass of copper sulfate was added to 427 parts by mass of pure water heated to 80 ° C., and the solution was completely dissolved and added to the above solution, and mixed by stirring. This preparation liquid (A) was dried by a spray drying method, and the obtained dried powder (B) was pre-fired at 350 ° C. for 4 hours to obtain a pre-fired body (C). The obtained pre-fired body (C) was pulverized in a ball mill to obtain a pre-fired powder (E). The median diameter of the obtained pre-fired powder (E) was 37.5 μm. 5% by mass of crystalline cellulose and 5% by mass of milled fiber EFH150-31 manufactured by Central Glass Co., Ltd. were added to the pre-calcined powder (E) and mixed thoroughly, and then the pre-calcined powder (E) was granulated by using a 20% by mass glycerin solution as a binder, and molded into a spherical shape on an inactive spherical carrier made of a mixture of silica and alumina so that the loading rate was 33% by mass. A liquid delivery pump with two flow paths was used to add the binder. FIG. 1 is a schematic diagram showing the binder addition method in Example 1, showing a top view of a rolling granulator 10. The rolling granulator 10 is charged with spherical carriers, and the carriers are agitated by rotating the bottom plate 11 clockwise as indicated by the arrow CW in FIG. 1. As shown in FIG. 1, granules containing the pre-calcined powder (E) were charged at position A on the bottom plate 11 of the rolling granulator 10 to which the spherical carriers were charged. A single binder addition port B was provided at a position 180 degrees and 270 degrees from the granule drop point A in the direction of rotation of the bottom plate 11 of the tumbling granulator 10, and the binder was dropped into the center of the doughnut-shaped catalyst band 20 that was generated when the bottom plate 11 rotated. The centrifugal acceleration at that time was 10G. Next, main calcination was carried out under conditions of 390° C. for 4 hours to obtain a spherical catalyst 1 of the present invention. The composition of catalyst 1 is Mo 12 V 3.0 W 1.2 Cu 1.2 Sb 0.50 It is.

[0052] [Example 2] <Catalyst 2 production> 148 parts by mass of ammonium paratungstate was completely dissolved in 5241 parts by mass of pure water heated to 95 ° C. While stirring this solution, 166 parts by mass of ammonium metavanadate and 1000 parts by mass of ammonium molybdate were added, and after confirming dissolution, 70.5 parts by mass of antimony acetate was gradually added and thoroughly stirred. Next, 143 parts by mass of copper sulfate was added to 427 parts by mass of pure water heated to 80 ° C., and the solution was completely dissolved. 16 parts by mass of 12 tungsto (IV) silicate 26 water dissolved in 50 parts by mass of pure water was added and stirred and mixed. This mixed liquid (A) was dried by spray drying, and the obtained dried powder (B) was pre-fired at 350 ° C. for 4 hours to obtain a pre-fired body (C). The obtained pre-fired body (C) was pulverized with a ball mill to obtain a pre-fired powder (E). The median diameter of the obtained pre-fired powder (E) was 28.6 μm. 5% by mass of crystalline cellulose and 5% by mass of milled fiber EFH150-31 manufactured by Central Glass Co., Ltd. were added to the pre-calcined powder (E) and mixed thoroughly, and then the mixture was granulated by rolling granulation using a 20% by mass glycerin solution as a binder, and the mixture was molded into a spherical shape so that the loading rate was 33% by mass on an inactive spherical carrier consisting of a mixture of silica and alumina. A single-flow liquid pump was used to add the binder, and a binder addition port was provided at a position 180 degrees ahead of the granule drop point A in the direction of rotation of the bottom plate 11 of the rolling granulator 10, and the binder was dropped into the center of the radial direction of the donut-shaped catalyst band 20 generated when the bottom plate 11 of the rolling granulator 10 rotated. The centrifugal acceleration at that time was 26 G. FIG. 2 is a schematic diagram showing the method of adding the binder in Example 2, and is the same as FIG. 1 except that the binder addition position B is different. Next, main calcination was carried out at 390° C. for 4 hours to obtain a spherical catalyst 2 of the present invention. The composition of catalyst 2 is Mo 12 V 3.0 W 1.3 Cu 1.2 Sb 0.50 S 0.010 It is.

[0053] [Example 3] <Catalyst 3 production> 148 parts by mass of ammonium paratungstate was completely dissolved in 5241 parts by mass of pure water heated to 95 ° C. While stirring this solution, 166 parts by mass of ammonium metavanadate and 1000 parts by mass of ammonium molybdate were added, and after confirming dissolution, 70.5 parts by mass of antimony acetate was gradually added and thoroughly stirred. Next, 143 parts by mass of copper sulfate was added to 427 parts by mass of pure water heated to 80 ° C., and the solution was completely dissolved. The mixture (A) was dried by a spray drying method, and the obtained dried powder (B) was pre-fired at 350 ° C. for 4 hours to obtain a pre-fired body (C). The obtained pre-fired body (C) was pulverized in a ball mill to obtain a pre-fired powder (E). The median diameter of the obtained pre-fired powder (E) was 28.2 μm. 5% by mass of crystalline cellulose and 5% by mass of milled fiber EFH150-31 manufactured by Central Glass Co., Ltd. were added to the pre-calcined powder (E) and mixed thoroughly, and then the mixture was subjected to rolling granulation, using a 20% by mass glycerin solution as a binder, and molded into a spherical shape so that the loading rate was 25% by mass on an inactive spherical carrier consisting of a mixture of silica and alumina. A single-flow liquid pump was used to add the binder, and a binder addition port was provided at a position 180 degrees ahead of the granule drop point A in the direction of rotation of the bottom plate 11 of the rolling granulator 10, and the binder was dropped onto the wall side of the rolling granulator 10 (the outer periphery of the catalyst band 20 in the radial direction) of the donut-shaped catalyst band 20 generated when the bottom plate 11 of the rolling granulator 10 rotated. The centrifugal acceleration at that time was 26G. FIG. 3 is a schematic diagram showing a method of adding a binder in Example 3, and is similar to FIG. 1 except that the position B where the binder is added is different. Next, main calcination was carried out under conditions of 390° C. for 4 hours to obtain a spherical catalyst 3 of the present invention. The composition of catalyst 3 was Mo 12 V 3.0 W 1.2 Cu 1.2 Sb 0.50 It is.

[0054] [Comparative Example 1] <Production of Catalyst 4> 148 parts by mass of ammonium paratungstate was completely dissolved in 5241 parts by mass of pure water heated to 95 ° C. While stirring this solution, 166 parts by mass of ammonium metavanadate and 1000 parts by mass of ammonium molybdate were added, and after confirming dissolution, 70.5 parts by mass of antimony acetate was gradually added and thoroughly stirred. Next, 143 parts by mass of copper sulfate was added to 427 parts by mass of pure water heated to 80 ° C., and the solution was completely dissolved. The mixture (A) was dried by a spray drying method, and the obtained dried powder (B) was pre-fired at 350 ° C. for 4 hours to obtain a pre-fired body (C). The obtained pre-fired body (C) was pulverized in a ball mill to obtain a pre-fired powder (E). The median diameter of the obtained pre-fired powder (E) was 29.8 μm. 5% by mass of crystalline cellulose and 5% by mass of milled fiber EFH150-31 manufactured by Central Glass Co., Ltd. were added to the pre-calcined powder (E) and mixed thoroughly, and then the mixture was subjected to rolling granulation, using a 20% by mass glycerin solution as a binder, and molded into a spherical shape so that the loading rate was 33% by mass on an inactive spherical carrier consisting of a mixture of silica and alumina. A single-flow liquid pump was used to add the binder, and a binder addition port was provided at a position 180 degrees ahead of the granule drop point A in the direction of rotation of the bottom plate 11 of the rolling granulator 10, and the binder was dropped at the center of rotation (the inner periphery of the catalyst band 20 in the radial direction) of the donut-shaped catalyst band 20 generated when the bottom plate 11 of the rolling granulator 10 rotated. The centrifugal acceleration at that time was 26 G. FIG. 4 is a schematic diagram showing the method of adding the binder in Comparative Example 1, and is the same as FIG. 1 except that the binder addition position B is different. Next, main calcination was carried out at 390° C. for 4 hours to obtain a spherical catalyst 4. The composition of catalyst 4 was Mo 12 V 3.0 W 1.2 Cu 1.2 Sb 0.50 It is.

[0055] [Comparative Example 2] <Production of Catalyst 5> 148 parts by mass of ammonium paratungstate was completely dissolved in 5241 parts by mass of pure water heated to 95 ° C. While stirring this solution, 166 parts by mass of ammonium metavanadate, 1000 parts by mass of ammonium molybdate, and 70.5 parts by mass of antimony acetate were gradually added and thoroughly stirred. Next, 143 parts by mass of copper sulfate was added to 427 parts by mass of pure water heated to 80 ° C., and the solution was completely dissolved and added to the above solution and mixed by stirring. This preparation liquid (A) was dried by a spray drying method, and the obtained dried powder (B) was pre-fired at 350 ° C. for 4 hours to obtain a pre-fired body (C). The obtained pre-fired body (C) was pulverized with a vibration mill to obtain a pre-fired powder (E). The median diameter of the obtained pre-fired powder (E) was 22.7 μm. 5% by mass of crystalline cellulose and 5% by mass of milled fiber EFH150-31 manufactured by Central Glass Co., Ltd. were added to the pre-calcined powder (E) and mixed thoroughly, and then the mixture was molded into a spherical shape by rolling granulation using a 20% by mass glycerin solution as a binder on an inactive spherical carrier consisting of a mixture of silica and alumina so that the loading rate was 33% by mass. A liquid pump was used to add the binder, and a binder addition point was provided at a position 240 degrees ahead of the granule drop point A in the direction of rotation of the bottom plate 11 of the rolling granulator 10, and the binder addition port was divided into six points in the radial direction of the donut-shaped catalyst band 20 generated when the bottom plate 11 of the rolling granulator 10 rotated, and the binder was dropped at a uniform flow rate from each of them. The centrifugal acceleration at that time was 4.2 G. FIG. 5 is a schematic diagram showing the binder addition method in Comparative Example 2, and is the same as FIG. 1 except that the binder addition position B is different. Next, main calcination was carried out at 375° C. for 4 hours to obtain a spherical catalyst 5. The composition of catalyst 5 was Mo 12 V 3.0 W 1.2 Cu 1.2 Sb 0.50 It is.

[0056] Oxidation reactions were carried out using the obtained catalysts 1 to 5. 67.6 ml of the catalyst was packed into a reaction tube with an inner diameter of 28.4 mm, and a gas having the following composition obtained by gas-phase catalytic oxidation of propylene using a molybdenum-bismuth catalyst was introduced into the reaction tube, and the reaction was carried out at an SV (space velocity; flow rate of raw material gas per unit time / apparent volume of packed catalyst) of 1020 / hr and a reaction bath temperature of 260°C. Acrolein 5.9vol% Unreacted propylene + other organic compounds 1.7 vol% Oxygen 4.7vol% Steam 17.2vol% Nitrogen-containing inert gas 70.5vol%

[0057] Table 1 shows the reaction results obtained by the oxidation reaction and the particle shape parameters of each catalyst obtained by dynamic image analysis using a Microtrack Bell CAMSIZER X2. [Table 1]

[0058] [Example 4] (Preparation of Catalyst 6) 100 parts by mass of ammonium heptamolybdate was completely dissolved in 380 parts by mass of pure water heated to 60°C (mother liquor 1). Next, 0.37 parts by mass of potassium nitrate was dissolved in 3.2 parts by mass of pure water and added to mother liquor 1. Next, nitric acid (60% by mass) was added to mother liquor 1 to make the pH = 4. Next, 36 parts by mass of ferric nitrate, 81 parts by mass of cobalt nitrate and 41 parts by mass of nickel nitrate were dissolved in 84 parts by mass of pure water heated to 60°C and added to mother liquor 1. Next, 16 parts by mass of bismuth nitrate was dissolved in an aqueous nitric acid solution prepared by adding 4.1 parts by mass of nitric acid (60% by mass) to 17 parts by mass of pure water heated to 60°C, and added to mother liquor 1. This mother liquor 1 was dried by a spray drying method, and the obtained dried powder was pre-calcined at 440°C for 4 hours. The median diameter of the pre-calcined powder thus obtained was 49.4 μm, and it was advanced to the next step without being pulverized. 5% by mass of crystalline cellulose was added to the pre-calcined powder, and after thorough mixing, the mixture was spherically supported on an inactive carrier consisting of a mixture of silica and alumina using a 33% by mass glycerin solution as a binder by the rolling granulation method so that the support rate was 50% by mass. A liquid pump was used to add the binder, and a binder addition point was provided at a position 240 degrees ahead of the granule drop point A in the direction of rotation of the bottom plate 11 of the rolling granulator 10, and the binder addition port was divided into two in the radial direction of the donut-shaped catalyst band 20 generated when the bottom plate 11 of the rolling granulator 10 rotated, and the binder was dropped at a uniform flow rate from each of them. The centrifugal acceleration at that time was 2.4 G. FIG. 6 is a schematic diagram showing the binder addition method in Example 4, and is the same as FIG. 1 except that the binder addition position B is different. Next, main calcination was carried out under conditions of 520° C. for 4 hours to obtain catalyst 6. The composition of catalyst 6 was Mo:Bi:Fe:Co:Ni:K=12:0.70:1.9:5.9:3.0:0.080.

[0059] An oxidation reaction was carried out using the obtained catalyst 6. 67.6 ml of the catalyst was packed into a reaction tube with an inner diameter of 22.2 mm, and a gas having the following composition was passed through the reaction tube at an SV (space velocity; flow rate of raw material gas per unit time / apparent volume of packed catalyst) of 862 / hr, and the reaction was carried out at a reaction bath temperature of 305°C. Propylene 8.3vol% Oxygen 14.1vol% Steam 24.8vol% Nitrogen 52.8vol%

[0060] The reaction results obtained by the oxidation reaction and the particle shape parameters of each catalyst obtained by dynamic image analysis using a Microtrack Bell CAMSIZER X2 are shown in Table 2. The reaction results were calculated using the following formula. Propylene conversion rate (%) = (number of moles of reacted propylene) / (number of moles of supplied propylene) x 100 Effective selectivity (%) = (total number of moles of acrolein and acrylic acid produced) / (number of moles of propylene reacted) x 100 [Table 2]

[0061] This application is based on Japanese patent application No. 2022-202843 filed on December 20, 2022, the contents of which are incorporated herein by reference. [Industrial Applicability]

[0062] According to the present invention, particularly when acrolein is used as a raw material and acrylic acid is produced by a gas phase catalytic oxidation reaction, the selectivity can be maintained high. Therefore, the plant for producing acrylic acid can be operated stably for a long period of time, which is very useful.

Claims

1. A spherical catalyst having a sphericity parameter SPHT3 value of 0.9822 or more and 0.9950 or less, as determined by particle shape measurement using a dynamic image analysis method, and a catalytically active component represented by the following formula (1): Here, the sphericity parameter SPHT3 is a value obtained by the following formula (I). (Mo) 12 (V) a (W) b (1) c (Sb) d (X) e (Y) f (Z) g (O) h (1) (In formula (1), Mo, V, W, Cu, Sb, and O represent molybdenum, vanadium, tungsten, copper, antimony, and oxygen, respectively; X represents at least one element selected from the group consisting of alkali metals and thallium; Y represents at least one element selected from the group consisting of magnesium, calcium, strontium, barium, and zinc; Z represents bismuth, tellurium, silver, selenium, silicon, aluminum, boron, niobium, cerium, tin, chromium, manganese, iron, cobalt, nickel, samarium, germanium, Each of them represents at least one element selected from the group consisting of zirconium, titanium, tantalum, lead, indium, sulfur, palladium, gallium, lanthanum, and arsenic. Also, a, b, c, d, e, f, g, and h represent the atomic ratio of each element, and a represents 1.0≦a≦5.0, b represents 0.50≦b≦3.0, c represents 0.50≦c≦3.0, d represents 0<d≦2.0, e represents 0≦e≦0.50, f represents 0≦f≦1.0, and g represents 0≦g<6.0, relative to 12 molybdenum atoms. Also, h represents the number of oxygen atoms required to satisfy the valence of each of the components. SPHT3 = 4πA ÷ P 2 ・・・(@) In the above formula (I), A is the area of ​​the particle photographed by dynamic image analysis, and P is the perimeter of said particle.

2. A spherical catalyst having a sphericity parameter SPHT3 value obtained by particle shape measurement using a dynamic image analysis method of 0.9822 or more and 0.9950 or less, and a catalytically active component represented by the following formula (2). Here, the sphericity parameter SPHT3 is a value obtained by the following formula (I). Mo 12 Bi b1 Ni c1 Co d1 Fe e1 X f1 Y g1 Z h1 O i1 ・・・(2) (In the formula, Mo, Bi, Ni, Co and Fe represent molybdenum, bismuth, nickel, cobalt and iron, respectively; X represents at least one element selected from tungsten, antimony, tin, zinc, chromium, manganese, magnesium, calcium, silicon, aluminum, cerium and titanium; Y represents at least one element selected from sodium, potassium, cesium, rubidium and thallium; Z represents an element belonging to Groups 1 to 16 of the periodic table; and and at least one element selected from elements other than Y, and b1, c1, d1, e1, f1, g1, h1, and i1 respectively represent the numbers of atoms of molybdenum, bismuth, nickel, cobalt, iron, X, Y, Z, and oxygen, and satisfy 0.50≦b1≦1.7, 1.0≦c1≦3.3, 5.0≦d1≦6.8, 0<c1+d1≦20.0, 1.0≦e1≦3.0, 0≦f1≦2.0, 0≦g1≦3.0, 0≦h1≦5.0, and i1 is a value determined by the oxidation state of each element.) SPHT3 = 4πA ÷ P 2 ・・・(@) In the above formula (I), A is the area of ​​the particle photographed by dynamic image analysis, and P is the perimeter of said particle.

3. 3. The catalyst according to claim 1 or 2, which is a catalyst in which a catalytically active component is supported on an inert carrier.

4. 4. The catalyst of claim 3, wherein the inert support is silica, alumina or a combination thereof.

5. The catalyst according to claim 1 or 2, which is used for producing an unsaturated aldehyde, an unsaturated carboxylic acid, or a conjugated diene compound.

6. A method for producing an unsaturated aldehyde, an unsaturated carboxylic acid, or a conjugated diene compound, using the catalyst according to claim 1 or 2.

Citation Information

Patent Citations

  • Catalyst and its production

    JP1996299797A

  • Catalyst

    JP2001079408A

  • Method for manufacturing catalyst for composite oxide

    JP2003251184A

  • Catalyst for manufacturing acrylic acid, method of manufacturing acrylic acid using catalyst and method of manufacturing water-absorbing resin

    JP2009214105A

  • Unsaturated carboxylic acid production process and supported catalyst

    JP2015096497A